2022
DOI: 10.3390/medicina58050611
|View full text |Cite
|
Sign up to set email alerts
|

ECMO and Impella Support Strategies as a Bridge to Surgical Repair of Post-Infarction Ventricular Septal Rupture

Abstract: Background and Objectives: Post-infarct ventricular septal rupture (PIVSR) continues to have significant morbidity and mortality, despite decreased prevalence. Impella and venoarterial extracorporeal membranous oxygenation (VA-ECMO) have been proposed as strategies to correct hemodynamic derangements and bridge patients to delayed operative repair when success rates are higher. This review places VA-ECMO and Impella support strategies in the context of bridging patients to successful PIVSR repair, with an addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Delay between electrocardiographic documentation of STEMI and subsequent development of VSR ( Table 2 ). Twenty patients (13 male) belonged to this category [ [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] ]. Their mean age was 66.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Delay between electrocardiographic documentation of STEMI and subsequent development of VSR ( Table 2 ). Twenty patients (13 male) belonged to this category [ [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] ]. Their mean age was 66.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, in the presence of severe hypotension, the systolic murmur of VSR “may be difficult to identify because turbulent flow across the defect is reduced” [ 61 ], and the same might also be true of the systolic murmur of PMR [ 62 ]. Clinicians should also be especially vigilant for “stepwise” evolution of VSR [ [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] ], whereby a patient with delayed presentation of STEMI initially presents without clinical or echocardiographic stigmata of VSR but subsequently experiences hypotension and/or increasing breathlessness signalling onset of VSR [ [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] ]. The onset of VSR, in such cases, is typically associated with new-onset pansystolic murmur.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies, including case reports and small clinical series, suggested that VA-ECMO is a strategy to improve hemodynamic derangements and allows for delayed surgical repair. [15] However, the left ventricular afterload is increased, and this could increase the shunt fraction in PIVSR. The feasibility and safety of VA-ECMO in PIVSR need more studies to be confirmed.…”
Section: Ventricular Septal Rupturementioning
confidence: 99%
“…Six days after surgery the Impella was explanted in the operating theatre. The delay of surgery is justified by better success rates for operative VSD closure in literature as the tissue friability is reduced [5] [6].…”
Section: Accepted Manuscriptmentioning
confidence: 99%